Strategizing for the bottom of the pyramid: an action research into a Mexican agribusiness - Rafael Jaime Hernandez; Late Lawson-Lartego; Lars Mathiassen; Sergio Quinonez-Romandia (My University, 2019)
Purpose While recent research has established that businesses can benefit from engaging with people at the bottom of the pyramid (BOP), the authors know little about the practices that managers can use to effectively strategize this ethically sound and financially attractive proposition and turn it into new business. Design/methodology/approach To address this gap, the authors reported on an action research study in which the authors collaborated with a major Mexican agribusiness, ANSA, to expand its market through value co-creation with the country’s poorest farmers. To shape the strategizing, the authors combined dynamic capability theory and options theory, and the authors used the asset hexagon framework to understand the BOP population’s needs. Findings The authors offer a detailed account of how ANSA’s management team collaborated downstream with distributors and farmers and upstream with suppliers to grow a new micro-franchise business that increases the well-being of the poorest farmers and creates additional business opportunities. The research describes how firms can strategize and implement new business ventures for co-creating value with the BOP population. The results are a process model and related propositions for strategizing value co-creation with BOP. Originality/value The authors offer new empirical insights, a grounded process model and model-related propositions on strategizing BOP options. As such, the study contributes to the BOP literature by joining critical ethics with actionable knowledge of how such efforts may unfold and by demonstrating how theory may be enacted and developed in the process.